2021
DOI: 10.3390/cells10040933
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as a Risk Factor for Severe COVID-19 and Complications: A Review

Abstract: Emerging data suggest that obesity is a major risk factor for the progression of major complications such as acute respiratory distress syndrome (ARDS), cytokine storm and coagulopathy in COVID-19. Understanding the mechanisms underlying the link between obesity and disease severity as a result of SARS-CoV-2 infection is crucial for the development of new therapeutic interventions and preventive measures in this high-risk group. We propose that multiple features of obesity contribute to the prevalence of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 186 publications
(238 reference statements)
3
51
2
4
Order By: Relevance
“…Diabetes mellitus has been largely associated to poorer outcomes in COVID-19 patients [reviewed in ( Huang et al, 2020b )], while contradictory results have been observed in cohorts under TCZ treatment ( Moreno-Pérez et al, 2020 ; Morrison et al, 2020 ; Desai et al, 2021 ). Obesity has been related to a higher risk of death in COVID-19 patients ( Demeulemeester et al, 2021 ) and may act as a cofounder or modifier variable for this finding. Unfortunately, as we collected the information retrospectively from clinical records where obesity was not codified, we could not analyze its effect in our death risk estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus has been largely associated to poorer outcomes in COVID-19 patients [reviewed in ( Huang et al, 2020b )], while contradictory results have been observed in cohorts under TCZ treatment ( Moreno-Pérez et al, 2020 ; Morrison et al, 2020 ; Desai et al, 2021 ). Obesity has been related to a higher risk of death in COVID-19 patients ( Demeulemeester et al, 2021 ) and may act as a cofounder or modifier variable for this finding. Unfortunately, as we collected the information retrospectively from clinical records where obesity was not codified, we could not analyze its effect in our death risk estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating endurance training into the daily routine of adults affects telomerase activity and telomere length [24] and protects against excessive chromosomal damage [57]. Indeed, many studies have shown a reduction in the number of hospitalisations and the risk of death in COVID-19 patients who had been exercising [58] and were not overweight [59,60]. In addition, aging of the immune system also affects both resistance to infections and the biological age of a person [22,61].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity was one of the most serious global problems defined as pandemic before COVID-19 pandemic [ 9 ]. And there is a consensus that obesity is associated with various acute or chronic diseases, and also increases risk of COVID-19 infection and complications [ 10 , 11 ]. Experts in child growth have been very concerned about the potential weight and height change among preschool children during school closures.…”
Section: Introductionmentioning
confidence: 99%